PENGEMBANGAN MODUL PEMBELAJARAN PADA MATERI BILANGAN BULAT DAN PECAHAN UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Buulolo , Siwika (Universitas Nias Raya, 2023)
The purpose of this research is to develop learning modules that are valid, practical and effective, and can increase students' interest in learning. This type of research is development research with a 4D model, namely Define, Design, Develop and Disseminate. The data analysis technique in this study is validity, practicality and effectiveness analysis. The results of module validation by the validator average value of 3.31